3.13 Consumption of crabs in the Mesolithic: sidestepping the evidence? (Scottish Archaeological Internet Reports, 2009)
It would be quite easy to dismiss crabs as a very minor resource in this midden assemblage based only on the quantity present and relative calorific contribution. However, other perspectives are possible which consider individual actions and day to day activities. This approach serves as a reminder that resources were transformed into food through the performance of procurement, preparation and consumption activities and through these actions social relationships were created and maintained.